About Frequency Characteristics of Electric Fields of Cylindrical Piezoceramic Antenna with Screen in the Form of an Open Ring Layer - Z.T. Gusak; A.G. Leiko (Журнал нано- та електронної фізики)
According to rigorous method of “related” fields the analytical expressions to describe electric fields of piezoceramic cylindrical antennas with screen in the form of an open ring layer of finite thickness was obtained. As a result of numerical analysis the quantity relations and the features of frequency characteristics of the electric current and the input impedance of the antenna with screen depending on the parameters of the antenna elements were found.